2002
DOI: 10.1038/modpathol.3880531
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Proliferative Activity Are Predictors of Patient Outcome for Low-Grade Endometrioid Adenocarcinoma But Not Papillary Serous Carcinoma of Endometrium

Abstract: On the basis of pathogenesis, two types of endometrial cancer can be recognized. Type 1 endometrial carcinomas are relatively indolent tumors that develop after prolonged estrogen stimulation, on a background of endometrial hyperplasia. Type 2 endometrial carcinomas are aggressive tumors that are not associated with hyperplasia or estrogen excess. The aim of this study is to evaluate the prognostic significance of tumor proliferative activity in early-stage endometrial cancer by using mitotic index and immunos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 42 publications
2
26
1
Order By: Relevance
“…2,4 A dualistic model of endometrial carcinogenesis is widely accepted. 5,[28][29][30][31][32][33][34] Most endometrial carcinomas are of type I, arising from precursor hyperplasia driven by estrogen excess. These tumors express ER and PR, may have microsatellite instability (20%), and may have PTEN mutation (40%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,4 A dualistic model of endometrial carcinogenesis is widely accepted. 5,[28][29][30][31][32][33][34] Most endometrial carcinomas are of type I, arising from precursor hyperplasia driven by estrogen excess. These tumors express ER and PR, may have microsatellite instability (20%), and may have PTEN mutation (40%).…”
Section: Discussionmentioning
confidence: 99%
“…We did not use MIB-1 (Ki67) immunostaining as we have previously shown that it shows only a weak correlation with mitotic activity in uterine serous carcinomas. 28 Additional markers included proteins implicated in regulation of hormone response (Gfi-1 47 ), markers of squamous differentiation (and thus possible markers of endometrioid cell type; CK5/6 and p63 48,49 ), and a protein associated with serous differentiation (B72.3 50 ). Not surprisingly, given the criteria for selection of the immunopanel, most markers studied were prognostically significant in univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of the mutation of PTEN remains controversial, since this has been found to be positively associated with prognosis, whereas the loss of expression and methylation of PTEN are negatively associated with prognosis (54). A high proliferative activity of tumor cells based on Ki-67 expression and the number of mitoses is associated with a poor prognosis in endometrial cancer; however, the multivariate survival analyses do not show concordant results, which may be due to technical differences in measuring Ki-67 (55,56). The loss of expression of Bcl-2 and the resultant reduced apoptosis are also associated with a poor prognosis (39).…”
Section: Biomarkers For Prognosis and Treatmentmentioning
confidence: 99%
“…1,50 High proliferation index by MIB-1 stain has been shown to be of prognostic significance in endometrial carcinomas in some studies, [51][52][53] whereas others have shown no prognostic significance of MIB-1 in high-grade carcinomas of the endometrium. 54 We use MIB-1 in endometrial cancers that show complete absence of staining for p53 (p53 null), a pattern that has been shown to correlate with the presence of frameshift or nonsense p53 mutations. If such tumors show a very high proliferative rate (480%), we favor a diagnosis of serous carcinoma in the appropriate clinical and morphologic context.…”
Section: Pfs -Morphologymentioning
confidence: 99%